ESTIMATION OF DENSITY AND POPULATION STRUCTURE OF ROSEWOOD IN PERU AND ITS IMPLICATIONS FOR COMMERCIAL EXPLOITATION - GUTIERREZ PERALTA, Harol (2023)
Rosewood (Aniba rosaeodora) is one of the most commercially valuable Amazonian tree species due to the extraction of its essential oil. Its trade is regulated by the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES). Historically, it has been threatened by commercial overexploitation to meet the demands of cosmetic markets, mainly in Europe. This research aims to gather primary information on the population of rosewood in areas with known exploitation in Peru, estimating its density and determining its population structure. Data from 111 hectares were analyzed, divided into three sample strips of 1 hectare each (1000 x 10 m), spaced 350 m apart, and randomly distributed in areas with a probable species distribution (>75% probability of occurrence). The densities found were 0.524 individuals per hectare and 0.547 individuals per hectare in Loreto and Ucayali, respectively. Based on these results, it can be concluded that natural populations of the species are not capable of sustaining a production cycle involving the extraction of adult individuals, and any form of extraction that involves complete tree removal would not be sustainable. One management alternative proposed is the promotion of plantations to reduce pressure on natural populations.